In silico screening and surface plasma resonance‐based verification of programmed death 1‐targeted peptides. (8th December 2019) - Zhang, Pengli; Li, Chengping; Ji, Xiaoyue; Gao, Mingjie; Lyu, Sifan; Dai, Xiaojun; Du, Jiangfeng
Abstract: Programmed death 1 (PD‐1) is a key immune checkpoint molecule. When it binds to programmed death‐ligand 1 (PD‐L1), it can negatively regulate the immune response. Therefore, blockade of the PD‐1/PD‐L1 interaction could unleash the power of immune system. Though successes achieved by anti‐PD‐1/PD‐L1 antibody drugs in clinical for various cancers, many intrinsic limitations of the high molecular weight drugs require alternatives such as peptide drugs and chemical compounds. In this study, we described a novel in silico approach which was used to screen peptides from PDB database and aimed to identify peptides that have potential to bind the PD‐L1 binding area of PD‐1 molecule. Based on the docking poses, eight peptides were synthesized and measured for their binding abilities by surface plasma resonance technique. The K D values of the synthesized peptides ranged from 10.0 to 133.0 μM. Furthermore, the binding mechanism between PD‐1 and the peptides was studied. In conclusion, we established a fast and reliable screening method for peptide discovery, which could be applied for identifying peptide inhibitors of various targets. The synthesized peptides could be served as starting points for designing PD‐1 drug for cancer immunotherapy. Abstract : We established a fast and reliable screening method for peptide discovery, which could be applied for identifying peptide inhibitors of various targets. The synthesized peptides could be served as starting points for designing PD‐1 drug for cancer immunotherapy.